MCQ_EE_ch05_QC

Download as pdf or txt
Download as pdf or txt
You are on page 1of 5

5 Harder Equations NF

Quick Check
NF
A Simultaneous Equations in Two Unknowns,
One Linear and One Quadratic
This type of simultaneous equations is usually in the form of:
ax + by = c
, where a, b, c, p, q and r are real numbers.
y = px2 + qx + r
Each solution are the coordinates of the point of intersection of the straight line ax + by = c and the
parabola y = px2 + qx + r.
This type of simultaneous equations can be solved by algebraic method (method of substitution) or
graphical method. Method of elimination DOES NOT work.

1. Algebraic method (Method of substitution)


Example

3x + y = 5
Solve .
y = 2x2 – 5x + 1
Solution

3x + y = 5....................(1)
y = 2x2 – 5x + 1...........(2) Reminder

The quadratic equation


Putting (2) into (1),
is always using y as the
3x + (2x2 – 5x + 1) = 5 subject. So, ‘change of
subject’ is not needed.
2x2 – 2x – 4 = 0
x2 – x – 2 = 0
By the quadratic formula and calculator,
∴ x = –1 or x = 2 Reminder
Putting x = –1 into (1), The simultaneous equations after substitution
will become a quadratic equation with x.
3(–1) + y = 5
The value of the discriminant (Δ) of the
y=8 quadratic equation shows the number of
solutions of the simultaneous equations.
Putting x = 2 into (1),
There will be 3 possible cases:
3(2) + y = 5 •• 2 solutions (Δ > 0);
y = –1 •• 1 solution (Δ = 0);
x=–1 x=2 •• No solution (Δ < 0).
The solutions are or .
y=8 y=–1

1
Mathematics Exam Elite – Multiple-choice Questions (Compulsory Part)

2. Graphical method
Example

3x + y = 5
Solve .
y = 2x2 – 5x + 1
Solution

3x + y = 5....................(1)
y = 2x2 – 5x + 1...........(2)
Plot the graphs of 3x + y = 5 and y = 2x2 – 5x + 1. The coordinates of the points of intersection are
the solutions to this simultaneous equations.
y
10
y = 2x2 – 5x + 1
8

x
–2 –1 O 1 2 3 4 5
–2
3x + y = 5
–4

x=–1 x=2
From the graph, the solutions are or .
y=8 y=–1

Reminder

The simultaneous equations will be finally transformed to a quadratic equation in one unknown. By
considering the value of the discriminant (Δ) of that quadratic equation, there will be 3 possible cases on
the graphs:

2 solutions (Δ > 0) 1 solution (Δ = 0) No solution (Δ < 0)


y y
y = px2 + qx + r y = px2 + qx + r
y y = px2 + qx + r
ax + by + c = 0

x x
O O
x
O
ax + by + c = 0

ax + by + c = 0

2
5 Harder Equations

NF
B Fractional Equations that can be transformed into
Quadratic Equations
Consider the following form of fractional equations:
p q
+ = r, where a, b, c, d, p, q, and r are real numbers.
ax + b cx + d
This type of fractional equations can be transformed into a quadratic equation.
Example

2 3
Solve – = 2.
3x – 5 2 x + 1
Solution
2 3 Reminder
– =2
3x – 5 2 x + 1
2 3 Multiply by the L.C.M.
(3x – 5)(2x + 1) – (3x – 5)(2x + 1) = 2(3x – 5)(2x + 1) of the two denominators
3x – 5 2x +1
to all the terms on both
2(2x + 1) – 3(3x – 5) = 2(3x – 5)(2x + 1) sides.
4x + 2 – 9x + 15 = 12x2 – 14x – 10 Be careful on the signs.
2
12x – 9x – 27 = 0
By quadratic formula and calculator, x = 1.92 or –1.17 (correct to 3 sig. fig.).

NF
C Exponential and Logarithmic Equations
1. Exponential equations
Exponential equations can be classified in the following two types:
Type Example Step

I. akx + m = p 1 3x = 81 Take logarithm on both sides and then


2 53x = 625 transform it into a linear equation.
3 25x –3 = 256

II. a2x + m + ax + n = p 32x + 3 + 3x + 1 – 1 = 0 Transform the exponential equation into


a quadratic equation by substituting ax
by another variable.

Example

1 Solve the equation 43x = 100.


Solution
43x = 100
log 43x = log 100
3x log 4 = 2
2
x = 3 log 4

x = 1.11 (correct to 3 sig. fig.)

3
Mathematics Exam Elite – Multiple-choice Questions (Compulsory Part)

2 Solve the equation 52x + 1 + 5x + 3 – 2 = 0.


Solution Reminder

52x + 1 + 5x + 3 – 2 = 0 1. The x terms and the constant terms in the


52x • 51 + 5x • 53 – 2 = 0 index parts must be separated.

5(5x)2 + 125(5x) – 2 = 0........................(*) 2. a 2x must be written in (a x) 2.

Let y = 5x. 3. a x is transformed to a new variable y.

(*) becomes 5y2 + 125y – 2 = 0. 4. All negative result should be rejected.


By quadratic formula and calculator, 5. Remember to replace y with a x at the end.
y ≈ 0.015 989 773 or
y ≈ –25.015 989 77 (rejected since 5x > 0)
∴ 5x ≈ 0.015 989 773
log 5x = log 0.015 989 773
x log 5 = log 0.015 989 773
log 0.015 989 773
x= log 5
x = –2.57 (correct to 3 sig. fig.)

2. Logarithmic equations
Some of the logarithmic equations can be transformed to linear or quadratic equations.

Type Example Steps

I. k log (ax + b) = p 1 log (2x + 1) = 5 Group up all the


2 3 log (5x – 2) = 1 constants on the right
hand side.
Leave the log term on the
left hand side.
Transform the
logarithmic equation
into a linear equation by
changing log a = b in the
form of a = 10b.

II. log (ax + b) + log (cx + d) = p log (2x + 1) + log (x – 5) = 2 Apply the properties of
logarithms to combine
the logarithmic terms
together.
Then solve it using the
method in type I.

4
5 Harder Equations

Example

1 Solve the equation log (3x + 5) = 2.


Solution
log (3x + 5) = 2
3x + 5 = 102
95
∴ x=
3
2 Solve the equation log (x – 4) + log (3x + 2) = 1. Reminder
Solution 1. Recall that log a + log b = log ab.
log (x – 4) + log (3x + 2) = 1 2. Check the solution. We have to
log [(x – 4)(3x + 2)] = 1 reject the solution if the value of the
(x – 4)(3x + 2) = 10 expression of the logarithmic term
2
3x – 10x – 18 = 0 is negative after substituting the
solutions.
By quadratic formula and calculator,
x ≈ 4.629 398 139 or x ≈ –1.296 064 806 (rejected as x – 4 < 0)
∴ x = 4.63 (correct to 3 sig. fig.)

NF D Other Equations
1. axm + bxn + c = 0, where a, b, c, m and n are real numbers and m = 2n.
Take the following steps:
i. Rewrite axm + bxn + c = 0 into ax2n + bxn + c = 0.
ii. Then, transform ax2n + bxn + c = 0 into a(xn)2 + bxn + c = 0.
iii. By substituting y = xn, the equation becomes ay2 + by + c = 0.
iv. The equation can be solved by the techniques of solving quadratic equations.
Remember to check the validity of the solutions (i.e. y > 0).

2. ax + b + cx + d = 0, where a, b, c and d are real numbers.


Take the following steps:
i. Rewrite ax + b + cx + d = 0 into ax + b = –cx – d.
ii. Take square on both sides,
( ax + b )2 = (–cx – d)2
The equation becomes
ax + b = c2x2 + 2cdx + d2
iii. After rearranging the terms in descending order of x, the equation can be solved by the
techniques of solving a quadratic equation.
Remember to check the validity of the solutions (i.e. ax + b > 0).

You might also like